Islamic Boarding Schools' Food Handlers' Awareness Of Food Safety Issues And Their Actions In Relation To e. Coli Contamination Of Food - Fitri Komala Sari; Nur Aini Mahmudah; Lulu’ Luthfiya; Fathimah Fathimah; Marya Ulfah (Poltekkes Kemenkes Mataram, 2023)
Background: E. coli can grow due to foodborne illnesses, and according to Islamic law, the food consumed is not tayyib. Food handlers, including those in Islamic boarding schools, must know about food safety to prevent foodborne illnesses.Research Methods: At the Boarding School in East Java, a food production facility was used for the research. This study has a cross-sectional design and is quantitative. The sample used a total sampling method with a total of 38 samples. The gathered information was evaluated using the Spearman test. E. coli testing at the Islamic boarding school using the MPN technique on six food samples and water sources. Research Result: 25 food handlers are between 18 and 35, while 13 others are between 36 and 55. Higher-educated food handlers are on par with less-educated ones. Most people who handled food did so with a solid awareness of the characteristics of food safety behavior and knowledge. It is also believed that food workers' safety conduct is good because of their generally positive or good demeanor. Two food samples, S1 with an MPN value of 6.1/g and S2 with an MPN value of 7.2/g contained E. coli. The link had a value of 0.67 and a Spearman's correlation value of 0.070, indicating a positive relationship with weak correlation strength. The findings showed that awareness of food safety was not related to the prevalence of E. coli, with p>0.05 and 0.123. Conclusion: There was a positive correlation of 0,070 and a value of 0,067, indicating no link between food safety knowledge and behavior. The existence of E. coli did not correlate with knowledge of food safety, with a value of 0,13 and a negative correlation of -0,255.